Prevalence and associated factors of visual impairment among adults aged 40 and above in Southern Ethiopia, 2022 - Tamiru Getachew Deme; Masresha Mengistu; Firdawek Getahun (Scientific Reports, 2024)
Abstract Visual impairment is a functional limitation of the eye caused by a disorder or disease that can reduce one’s ability to perform daily activities. Many studies in Ethiopia have focused on childhood visual impairments. We assessed the prevalence and factors associated with visual impairment among adults aged 40 and above. Community-based cross-sectional study was done and a systematic sampling technique was used to select 655 participants. Data were collected by interviewer administered questionnaire, E-Snell chart, pinhole, torch light, and magnifying loupe. SPSS version 25 was used for analysis. Bivariate and multivariate analyses were performed to identify factors associated with outcome variable. The overall prevalence of visual impairment was found to be 36.95% (95% CI 33.2–40.8%). Factors associated with a higher odds of visual impairment included aged 51–60 years (AOR 2.37, 95% CI 1.29–4.44), aged 61 and above (AOR 8.9, 95% CI 4.86–16.3), low wealth index (AOR 1.91, 95% CI 1.14–3.2), divorced and widowed (AOR 4.67, 95% CI 2.77–7.86), no formal education (AOR 14.28, 95% CI 2.82–71.46), not utilizing eyeglass (AOR 3.94, 95% CI 1.65–9.40). The prevalence of visual impairment was relatively high compared to other studies. Age, marital status, occupation, educational status, wealth index, and not using eyeglasses were significantly associated with visual impairment. Refractory error is the leading cause of visual impairment. Early eye care service interventions are needed in this area.